INVOLVEMENT OF FUNCTIONAL SYSTEMS (ANALYZERS) IN MAINTAINING BALANCE (Conferencea, 2023)
The process of maintaining balance is very complex, and a complex of all analyzers that make up a single mechanism is involved in this process.